2010
DOI: 10.1074/jbc.m109.041004
|View full text |Cite
|
Sign up to set email alerts
|

NF45 and NF90 Regulate HS4-dependent Interleukin-13 Transcription in T Cells

Abstract: Expression of the cytokine interleukin-13 (IL13) is critical forThe T cell-derived cytokine interleukin (IL) 2 -13 plays a pivotal effector role in T helper type 2 (Th2) immune responses to extracellular parasites (1). When dysregulated by genetic and/or environmental factors, IL13 expression is essential for the pathogenesis of allergic diseases (2). Indeed, experimental animal models have shown that IL-13 is necessary and sufficient to induce all the cardinal features of allergic lung inflammation, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 53 publications
(75 reference statements)
0
57
0
Order By: Relevance
“…The NF45/NF90 heterodimer has been previously implicated in a plethora of cellular pathways (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The involvement of NF45/NF90 in ribosome synthesis identified here adds a very basic cellular pathway to its functional repertoire and could well explain why NF90 is essential in vertebrates.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The NF45/NF90 heterodimer has been previously implicated in a plethora of cellular pathways (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The involvement of NF45/NF90 in ribosome synthesis identified here adds a very basic cellular pathway to its functional repertoire and could well explain why NF90 is essential in vertebrates.…”
Section: Discussionmentioning
confidence: 64%
“…Over recent years, NF45/NF90 has been implicated in a great variety of biological processes. Apart from regulation of transcription (5)(6)(7), the heterodimer has also been linked to numerous other pathways, such as DNA damage response (8,9), mRNA metabolism (10,11), microRNA (miRNA) biogenesis (12), and viral infection (13)(14)(15)(16)(17). NF90 knockout mice display severe defects in skeletal muscle formation leading to respiratory failure soon after birth (18), indicating an essential role of NF90 function in vertebrate development.…”
mentioning
confidence: 99%
“…NF45 was first identified as a nuclear factor of activated T cells (NFAT)-related transcription factor that regulates interleukin-2 transcription, together with its binding partner NF90 (8). Therefore, a general reduction in the polysome loading of APAF1 could reflect an indirect transcriptional effect of NF45 and its binding partner, NF90, in a complex that is known to target a wide array of genes (9,45). Moreover, we showed previously that the attenuation of cIAP1 IRES-dependent translation induction in d5 cells during ER stress can be rescued by reexpression of NF45 but not NF90 (7); this further argues that the NF45-NF90 transcriptional effects are independent of the function of NF45 as an ITAF.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NF45 was shown to interact directly with the cIAP1 IRES and positively affect its activity, resulting in the increased translation of its mRNA during thapsigargin-induced endoplasmic reticulum (ER) stress. This was the first report of NF45 having a bona fide function in IRESmediated translation, although there have been reports of the involvement of NF45 and its binding partner NF90 in transcription (8,9), viral replication (10)(11)(12), and microRNA processing (13,14).…”
mentioning
confidence: 98%
“…We previously showed that the NF90-NF45 complex suppresses pri-miRNA cleavage and mature miRNA production through binding to pri-miRNAs in HEK293T cells (27). In addition, it has been reported that NF90 or the NF90-NF45 complex is involved in mRNA stabilization (28), translational repression (29,30), replication of viral RNA (31), and transcription (32,33) in vitro. However, the physiological functions of NF90 and/or NF45 remain largely unknown because NF90 or NF45 knockout (KO) mice exhibit perinatal lethality due to respiratory failure or embryonic lethality (32,34).…”
mentioning
confidence: 99%